2017
DOI: 10.1007/s10792-017-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of hyperopia and choroidal thickness, vessel diameter and area

Abstract: Macular choroid thickens as the hyperopic error increases as well as axial length decreases in short eyes. The diameters and areas of noticeable large choroidal vessels in EDI-OCT also increase. These findings in EDI-OCT measurements may play a role in developing population nomograms, as a correcting parameter and in understanding the pathophysiology of certain diseases in short eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
11
2
Order By: Relevance
“…It has been previously reported that an increased macular choroidal thickness correlates with hypermetropia, so in consequence it correlates with a short AL [17, 18]. However, other studies, including our study, show that CT of hypermetropic anisometropic amblyopic eyes is thick, even when the difference in the AL or refractive error between amblyopic and fellow eyes is taken into account in the statistical analysis [10, 12, 19].…”
Section: Discussioncontrasting
confidence: 41%
“…It has been previously reported that an increased macular choroidal thickness correlates with hypermetropia, so in consequence it correlates with a short AL [17, 18]. However, other studies, including our study, show that CT of hypermetropic anisometropic amblyopic eyes is thick, even when the difference in the AL or refractive error between amblyopic and fellow eyes is taken into account in the statistical analysis [10, 12, 19].…”
Section: Discussioncontrasting
confidence: 41%
“…They believed that, in the early stages of myopia, choroidal thinning occurred before retinal thinning. Kaderli et al [ 25 ] found that the macular choroid thickened with an increase in hyperopia and a decrease in AL. At the same time, their study also found that the diameter and area of blood vessels in the macular choroid also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors such as age, axial length, refractive error, and race can affect the choroidal thickness measurements. [ 16 17 18 ] In this study, the control subjects were matched with the cases for age, sex, and axial lengths. Thus, it is unlikely that the wide range of refractive errors in our cases could have contributed to the significant difference in the choroidal thickness between the case and control groups.…”
Section: Discussionmentioning
confidence: 99%